2008
DOI: 10.1063/1.2999584
|View full text |Cite
|
Sign up to set email alerts
|

Cavity-enhanced stimulated emission cross section in polymer microlasers

Abstract: We report a cavity quantum electrodynamic enhancement of stimulated emission in polymer microlasers. The enhancement of the stimulated emission cross section is shown through the demonstration of laser action in the 40μm diameter cylindrical microcavities whose total molecular population density is below that theoretically required for the onset of lasing. The lower bound of the enhancement factor is estimated to be 3.9 based on the noncavity value of the stimulated emission cross section and the measured cavi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 15 publications
0
7
0
Order By: Relevance
“…It is noteworthy that, contrary to the seminal work of Yokohama et al [39], most of recently reported rate-equation models mainly focus on the enhancement of spontaneous emission [13], [29], [30], neglecting that stimulated emission is directly linked to spontaneous emission, as it is readily seen in the Einstein's relations or by the derivation of the light-matter interaction in the quantized field picture. Several experimental studies also report the enhancement of the stimulated emission, like for example in microdroplets [50], microlasers [51], and nanowire lasers [52], confirming that it should be treated on the same footing as the spontaneous emission. In the case of a nanolaser, this can result in a Purcell enhancement of the stimulated emission which influences the threshold of the laser, as theoretically investigated in the case of spectrally-narrow emitters [53], and as reported in a recent experimental work on subwavelength red-emitting hybrid plasmonic lasers [54].…”
Section: Introductionmentioning
confidence: 70%
“…It is noteworthy that, contrary to the seminal work of Yokohama et al [39], most of recently reported rate-equation models mainly focus on the enhancement of spontaneous emission [13], [29], [30], neglecting that stimulated emission is directly linked to spontaneous emission, as it is readily seen in the Einstein's relations or by the derivation of the light-matter interaction in the quantized field picture. Several experimental studies also report the enhancement of the stimulated emission, like for example in microdroplets [50], microlasers [51], and nanowire lasers [52], confirming that it should be treated on the same footing as the spontaneous emission. In the case of a nanolaser, this can result in a Purcell enhancement of the stimulated emission which influences the threshold of the laser, as theoretically investigated in the case of spectrally-narrow emitters [53], and as reported in a recent experimental work on subwavelength red-emitting hybrid plasmonic lasers [54].…”
Section: Introductionmentioning
confidence: 70%
“…8 This work simply assumed that the necessary condition was fulfilled and did not treat the eDOS. On the experimental side, cavity-enhanced StE was observed with lasing in rhodamine6G-ethanol droplets 7 and in polymer microrings, 6 materials with insufficient gain for lasing in the absence of gain enhancement.…”
mentioning
confidence: 97%
“…The the cavity. It is important to point out that experimental investigations related to both, dielectric microlasers [44,45] and plasmonic lasers [32,33], have reported an enhancement in the stimulated emission rate resulting from the Purcell effect, whereby the gain provided by the molecular medium is enhanced by a factor equal to the Purcell factor of the cavity [44]. As this effect is not completely taken into account in our simulations, and our structure exhibits an averaged Purcell factor of ∼ 2.2 over the gain medium (see supplementary material), we expect that the molecular concentration and pump requirements predicted by our simulations are overestimated.…”
Section: B Active Structurementioning
confidence: 99%